2020
DOI: 10.1038/s41598-020-73682-0
|View full text |Cite
|
Sign up to set email alerts
|

SNP-SNP interactions of oncogenic long non-coding RNAs HOTAIR and HOTTIP on gastric cancer susceptibility

Abstract: Genetic variants within oncogenic long non-coding RNAs HOTAIR and HOTTIP may affect their gene expression levels, thereby modifying genetic susceptibility to gastric cancer (GC). In a hospital-based study in Ardabil—a very high-risk area in North-West Iran, 600 blood samples from 300 GC patients and 300 healthy controls were recruited for genotyping. Seven HOTAIR (i.e., rs17720428, rs7958904, rs1899663, and rs4759314) and HOTTIP (i.e., rs3807598, rs17501292, and rs1859168) ‘tag’ single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Each model provides different assumptions regarding the genetic effect. Using the SNPStats, haplotype frequencies were also obtained for ACE2 and AGTR1 according to the expectation maximization algorithm [25]. Statistical analyses were done by SPSS version 23.0 (IBM, Chicago, USA).…”
Section: Statistical and Bioinformatics Analysismentioning
confidence: 99%
“…Each model provides different assumptions regarding the genetic effect. Using the SNPStats, haplotype frequencies were also obtained for ACE2 and AGTR1 according to the expectation maximization algorithm [25]. Statistical analyses were done by SPSS version 23.0 (IBM, Chicago, USA).…”
Section: Statistical and Bioinformatics Analysismentioning
confidence: 99%
“…For example, the CC genotype of rs920778 polymorphism was significantly associated with breast cancer risk in Turkish population, but no such association was found in Chinese samples [ 82 , 83 ]. Similarly, the T allele of rs12826786 can increase the risk of gastric cancer and adenocarcinoma in Chinese population [ 80 , 84 ]. But the same mutation found in the Turkish population is not associated with genetic susceptibility to gastric cancer, which may be due to differences in race and genetic background [ 78 ].…”
Section: The Relationship Between Hotair and Tumor Genetic Susceptibilitymentioning
confidence: 99%
“…Moreover, in a hospital-based case-control study, the rs7958904 HOTAIR SNP was found to increase gastric cancer risk by 1.57-fold. Additionally, the authors reported a possible interaction between HOTAIR rs7958904 and HOTTIP rs1859168 polymorphisms that significantly increased gastric cancer risk[ 39 ]. Similarly, recently rs7958904 G>C has been associated with colorectal cancer prevalence and mortality[ 34 ], and CC rs7958904 genotype has been also linked with increased breast cancer risk compared to the GG homozygo-tes[ 40 ].…”
Section: Discussionmentioning
confidence: 99%